2013
DOI: 10.1007/s00246-012-0628-6
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Aortic Flow Velocity Integral in 1193 Healthy Infants, Children, and Adolescents to Quickly Estimate Cardiac Stroke Volume

Abstract: The aortic velocity time integral (VTI) is an echocardiographic tool used to estimate cardiac output (CO) by multiplying it with the aortic valve (AV) area and heart rate (HR). Inaccurate measurement of AV diameter will lead to squared miscalculation of CO. The aortic VTI itself can serve as a left-ventricular (LV) output parameter. The normal range of aortic VTI in adulthood is relatively stable, compared with childhood, but reference data are lacking. The aim of this study was to establish reference values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
4
29
0
1
Order By: Relevance
“…In agreement with Pees et al findings, we found that sex‐related RIs for LVOT‐VTI data were not necessary. On the contrary, as was described, VTI and BSA were associated and BSA should be considered when analyzing VTI data.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with Pees et al findings, we found that sex‐related RIs for LVOT‐VTI data were not necessary. On the contrary, as was described, VTI and BSA were associated and BSA should be considered when analyzing VTI data.…”
Section: Discussionsupporting
confidence: 93%
“…Related with that, Poutanen et al found that increases in aortic VTI and those in BSA were associated in healthy subjects (n = 168; 11.1 ± 5 years). Pees et al also reported a strong correlation between aortic VTI and BSA in infants, children, and adolescents (n = 1200) distributed in 15 BSA groups (from 0.11 to 2.23 m 2 ) . In the present work, healthy children, adolescents, and young adults within a wide BSA range (mean 1.65 ± 0.26 m 2 , range from 0.75 to 2.44 m 2 ) were studied and the associations between hemodynamic data and BSA were analyzed (assessing the potential role of BSA as an explanatory factor).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, differences in cardiovascular physiology are usually reported between population of children under and over 6 months of age. Indeed, Pees C. et al showed in a retrospective analysis of 1223 echocardiographic examinations of healthy awake children (age 0‐20 years) that the aortic VTI ranged from 13.8 cm in neonates to 25.1 cm in children >17 years of age . For these reasons, we cannot currently recommend using VTI at baseline to guide the use of fluid challenge in children.…”
Section: Discussionmentioning
confidence: 99%